To What Extent Does the Use of Formative Assessment Foster Third Graders' Meaningful Learning in an EFL Class? (2018)
ABSTRACT: This action-research project was implemented to evaluate the effectiveness of using formative assessment to foster meaningful learning in third graders at Institución Educativa Francisco Miranda. The data were gathered through the teacher's journal, a students focus group, an interview to the cooperating teacher, and two assessment activities. An analysis of the collected data revealed that the quality of feedback is a key factor for formative assessment processes as well as authenticity and intentionality for learning to become meaningful. Some students used their feedback to improve their English performance; however, this performance is directly affected by the students' motivations and other factors such as the number of students per group, time constraints, and practicality.